Overcoming learning disabilities : - Akhutina, T. V. (Cambridge University Press, 2012)
"This book is dedicated to methods of preventing or overcoming learning disabilities based on the ideas of the great Russian psychologists Lev Vygotsky and Alexander Luria. The typical forms of learning disablities are described, and the effective methods of remediation of attention, executive functions (working memory and cognitive control), spatial and visual-verbal functions are discussed in details, The book has many illustrations of typical errors of children with learning disabilities and examples of remedial tasks. The book is useful for qualified psychologists and students, teachers and parents of children with learning disablities"--Provided by publisher.